Barriers in inclusive education in the Republic of Macedonia - Chichevska Jovanova, Natasha; Dimitrova Radojichikj, Daniela (НУ-УБ „Гоце Делчев“ Штип, 2014)
Inclusive education should enable equal participation of all students in regular schools and achievement of their maximum potentials in all aspects of education. To achieve this, i.e. to increase the participation and learning of students with disabilities, it is necessary to identify and eliminate the obstacles they encounter. The obstacles that hinder or prevent the inclusive process can be divided into three groups: psycho-social, physical and institutional. Teachers from mainstream schools often cite three reasons why they do not want to work with students with disabilities: many teachers feel they are not sufficiently prepared to deal with this category of children, or that they do not know their specific characteristics and therefore the special needs they have; many of them believe that inclusion is "enrollment" of a student with disabilities in the classroom without having assistance, additional equipment or support of any nature; a significant number of teachers fear that if a child with disabilities is included in their class, their work in the class will be more difficult and that it will take most of the time in the classroom, and thus students without disabilities will be neglected. Although most of the obstacles have been identified, and there are some legal solutions for some of them, it is necessary to make a list of priorities and determine the initial steps in the process of creating inclusive education in Macedonia.
Бариери во инклузивното образование во Република Македонија
Keywords: students with disabilities, teachers, mainstream schools